Change in daily energy intake associated with pairwise compositional change in carbohydrate, fat and protein intake among US adults, 1999–2010. Issue 8 (5th September 2014) - An, Ruopeng; Burd, Nicholas A
Abstract: Objective: To assess the change in daily energy intake associated with pairwise compositional change in carbohydrate, fat and protein intake among US adults stratified by sex, race/ethnicity and weight status. Design: Linear mixture model was performed to estimate the relationship between daily energy intake and macronutrient composition, adjusted for age and alcohol consumption, and accounting for survey design. Setting: Study sample from the National Health and Nutrition Examination Survey, 1999–2010 waves. Subjects: A total of 27 589 US adults aged 20 years and older were included in the study. Dietary macronutrient intake was calculated from 24 h dietary recall and BMI from objectively measured weight/height. Results: Across all population subgroups, substituting protein or carbohydrate for fat and substituting protein for carbohydrate were associated with decreased daily energy intake, with the largest effect resulting from substituting protein for fat. A 1 % increase in the percentage of energy from protein substituted for a 1 % decrease in the percentage of energy from fat was associated with a decrease in daily energy intake of 268·2 (95 % CI 169·0, 367·4) kJ, 289·5 (95 % CI 215·9, 363·2) kJ and 293·7 (95 % CI 210·0, 377·4) kJ among normal-weight (18·5≤BMI, kg/m 2 <25·0), overweight (25·0≤BMI, kg/m 2 <30·0) and obese (BMI≥30·0 kg/m 2 ) men, and 177·4 (95 % CI 130·5, 224·3) kJ, 188·7 (95 % CI 139·3, 238·1) kJ and 204·2 (95 % CI 158·2, 250·2) kJ among normal-weight, overweight and obese women, respectively. The relationship between macronutrient composition and daily energy intake varied substantially across sex, race/ethnicity and weight status. Conclusions: Policies promoting higher daily protein intake at the expense of lower fat intake could be effective in reducing total energy intake among US adults.